An Analysis of Religious Tourist Growth in Nepal - Sutihar, Deo Narayan (Economic Literature, 2016)
This article attempts to estimate annual growth rate of religious tourist to total tourist arrival ratio in Nepal, test the significance of annual growth rate of this ratio and evaluate the presence of auto-correlation among error terms using time series data of the ratio of religious tourist to total tourist arrival in Nepal from 1992 to 2010. The calculation of t-statistic exhibits that the growth rate of religious tourist to total tourist arrival ratio is significant. The D-W test shows that there is existence of positive auto- correlation among error terms. To remove the auto-correlation, the transformed variables have been used to estimate transformed equation of straight line and then it is found that there is no existence of auto-correlation among error terms after transforming the original data. Economic Literature, Vol. XI (20-25), June 2013